Myocardial deformation parameters predict outcome in patients with repaired tetralogy of Fallot. Issue 3 (29th December 2015) - Orwat, Stefan; Diller, Gerhard-Paul; Kempny, Aleksander; Radke, Robert; Peters, Brigitte; Kühne, Titus; Boethig, Dietmar; Gutberlet, Matthias; Dubowy, Karl-Otto; Beerbaum, Philipp; Sarikouch, Samir; Baumgartner, Helmut; et al.
Abstract : Background: Parameters of myocardial deformation have been suggested to be superior to conventional measures of ventricular function and to predict outcome in repaired tetralogy of Fallot (ToF). We aimed to test the hypothesis that parameters of myocardial deformation on cardiac MRI (CMR) relate to symptoms and provide prognostic information in patients with repaired ToF. Methods and results: We included 372 patients with ToF (median age 16 years; 55% male), recruited within a nationwide, prospective study. Longitudinal (LS), circumferential (CS) and radial global strain (RS) were analysed by CMR-based feature tracking (FT). A combined endpoint of death, successful resuscitation or documented ventricular tachycardia was employed. Parameters of global strain were associated with New York Heart Association (NYHA) class and symptomatic deterioration. During a median follow-up of 7.4 years, 20 events occurred. Left ventricular (LV) CS and right ventricular (RV) LS emerged as predictors of outcome, independent of QRS duration, LV/RV ejection fraction and volumes, NYHA class and peak oxygen uptake. In combination, these parameters also identified a subgroup of patients at significantly increased risk of adverse of outcomes (HR 3.3, p=0.002). Furthermore, LV LS, RS, CS and RV LS were related to the risk of death and nearly missed death (p<0.05 for all). Conclusions: FT-CMR provides myocardial deformation parameters, easily derived from standard CMR studies. They relate to symptoms and clinical deterioration in patients with ToF. More importantly, they predict adverse outcome independent of established risk markers, and should be considered as a useful adjunct to established outcome predictors, especially in younger patients with ToF. Clinical trial registration number: http://www.clinicaltrials.gov : NCT00266188 ; Results.